Pemanfaatan Coconut Dust dalam Kotak Kayu Sengon sebagai Peredam Kebisingan MEsin Diesel Penggilingan Padi di Usaha Dagang (UD) Sumber Barokah - Octavia Sakti Wulandari; Sri Muryani; Yamtana Yamtana (Poltekkes Kemenkes Yogyakarta, 2016)
The measurement of noise intensity in Sumber Barokah rice mill that located ion Ceper, Klaten,was 90,92 dB (A). According to the regulation issued by the Ministry of Manpower and Transmigration No. Per.13/Men/X/2011, the threshold limit value (TLV) of noise in workplace is 85 dB (A)within an exposure period of 8 hours per day. Noise intensity noise in work environment that exceed the quality standard can give negative effect for workers’ health. The purpose of this research was to use coconut dust placed in a sengon wooden box as noise silencer for rice millingdiesel engines. The research type was an experiment with one group pre-test post-test design.The research objects were two diesel engines used by Sumber Barokah. The noise measurement was using sound level meter at four points of 1-3 m distance from the engines, and eachpoint was measured three times. The average of noise intensity before the silencer was installedwas 94.86 dB (A) and afterward it decline to 83.94 dB (A) or has 11,70 dB (A)/12.40 % reduction.The paired t-test analysis at 9 % level of significance obtained a p-value less than 0.001 whichmeans that the reduction is statistically significant. Therefore, it can be concluded that coconutdust in sengon wooden box is beneficial for lowering the noise come from rice milling diesel engines.